Удосконалення системи оцінки ризику дефолту кредитного портфеля комерційного банку - Кочорба, Валерія Юріївна; Коломієць, Юлія Юріївна; Kochorba, Valeriia; Kolomiiets, Yuliya (Одеса : Гельветика, 2024)
Мета дослідження: удосконалення системи оцінки ризику дефолту кредитного портфеля комерційного банку за допомогою сучасних методів аналізу та прогнозування кредитних ризиків. У статті здійснено аналіз наукової літератури з питань управління кредитними ризиками, досліджено емпіричні дані про кредитний портфель комерційного банку, застосовано метод Value-at-Risk (VaR) для оцінки кредитного ризику, розроблено моделі оцінки ймовірності дефолту позичальника за допомогою логіт-моделі, здійснено моделювання кредитного ризику портфеля методом Монте-Карло. Запропонована система оцінки ризику дефолту кредитного портфеля дозволяє банкам більш точно оцінювати кредитні ризики, приймати обґрунтовані рішення щодо надання кредитів, мінімізувати збитки та підвищити прибутковість кредитної діяльності. Ефективна система оцінки ризику дефолту кредитного портфеля дозволить банкам мінімізувати збитки, підвищити прибутковість кредитної діяльності та зміцнити довіру клієнтів.

This research aims to improve the credit portfolio default risk assessment system of a commercial bank using modern credit risk analysis and forecasting methods. The paper analyzes scientific litera ture on credit risk management. It identifies several key elements of a bank`s credit risk management system: identification of credit risk factors, credit risk assessment, development of credit risk protec tion methods, credit risk monitoring and control, and credit risk management efficiency assessment. The factors of credit risk occurrence and their assessment methods are considered. Empirical data on the credit portfolio of a commercial bank are investigated. The Value-at-Risk (VaR) method is applied to assess credit risk. Credit risk under VaR is the maximum possible loss of a bank on a credit port folio at a given confidence level. The estimated amount of losses with a confidence probability is compared with the losses of the credit portfolio over a certain period of time. The paper develops models for assessing the probability of borrower default using a logit model. The Monte Carlo statistical simulation method is used to construct a credit loss distribution curve and simulate portfolio credit risk. The study is based on data on the credit history of borrowers of one of the Ukrainian banks for the period from 2020 to 2023. The analysis was carried out using the methods of mathematical statistics. To build a credit risk assessment model with the implementation of the VaR model, data on loans issued by a commercial bank to individuals were processed. The volume of the analyzed sample was 1000 loans. The following information was known for each borrower: the amount of the received loan; its internal credit rating and other information. The empirical distribution function allows for credit portfo lio risk assessment based on the Value-at-Risk methodology. The proposed credit portfolio default risk assessment system allows banks to more accurately assess credit risks, make informed decisions on lending, minimize losses, and increase the profitability of lending activities. An effective credit portfolio default risk assessment system will allow banks to minimize losses, increase the profitability of lending activities, and strengthen customer confidence.
Improvement of the credit portfolio default risk assessment system of a commercial bank
Електронний науково-практичний журнал. Наукове видання
Keywords: SOCIAL SCIENCES::Business and economics; SOCIAL SCIENCES::Other social sciences::Public sector research; банківські ризики; кредитний ризик; дефолт; кредитний портфель; Value-at-Risk; логіт-модель; метод Монте-Карло; credit risk; credit portfolio; default risk; logit model; Monte Carlo simulation; commercial bank